Sodium Meta Silicate Doped PPy and PT Composites with Giant Dielectric Constant - Erdonmez, Seda; Karabul, Yasar; Bulgurcuoglu, Ayse Evrim; Kilic, Mehmet; Ozdemir, Zeynep Guven; Icelli, Orhan (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2017)
In recent years, scientists have focused on searching new dielectric materials due to increasing necessity of high dielectric constant materials for microelectronic applications. Especially, developing a new high dielectric constant materials with low cost and weight has a crucial role in power electronic systems. From this point of view, conducting polymer/mineral composites have been prepared for achieving high dielectric constant material in this work. The dielectric and ac conductivity properties of the polypyrrole/sodium metasilicate (PPy/Na2SiO3) and polythiophene/sodium metasilicate (PT/Na2SiO3) composites have been determined by impedance spectroscopy measurements performed between 100 Hz-15 MHz. The highest dielectric constants have been obtained as 10(5) and 10(7) for PPy and PT composites with weight percentages of 10% and 50% Na2SiO3 doping, respectively. The relaxation mechanism of the composites have also been analyzed by the frequency dependence of imaginary component of complex electrical modulus. In addition, ac charge carrier transport mechanism of the samples have been investigated.
Keywords: Dielectric material; Conducting polymers (CP); Sodium metasilicate; AC conductivity; FREQUENCY-DEPENDENT CONDUCTIVITY; AC-CONDUCTIVITY; POLYMER; NANOCOMPOSITES; POLYPYRROLE; MODULUS; Engineering; Physics